Exploring gated eco-developments - contributing towards urban performance and sustainability: a case study of Chapman's Bay Estate, Noordhoek, Cape Town - Von Geusau, Alexa (School of Architecture, Planning and Geomatics, 2018)
South African cities maintain an apartheid legacy through their spatial layout, which is characterised by sprawl, fragmentation and separation. These characteristics have devastating implications for spatial justice, which cannot be isolated from urban performance and sustainability. Yet, the proliferation of gated developments and eco-estates is becoming an increasingly popular form of development both internationally and within South Africa. Often the sustainability debate allows for the glossing over of issues of social justice. These exclusive enclaves act as a microcosm for broader issues of social polarization and ecological fragmentation. This dissertation explores the complexities of this radical urban form and its implications for urban performance and sustainability. Through an understanding of the drivers and consequences of gating, it explores the conflict in which planners often find themselves: between the ideals of an integrated, accessible city and the contextual realities. This study of gated developments has been founded upon a theoretical debate as well as a case study analysis of Chapman's Bay Estate in Noordhoek, Cape Town, South Africa. This included a spatial and legislative analysis of the CoCT's Gated Development Policy as well as relevant spatial plans, through the lens of Chapman's Bay Estate. The research has revealed the perpetuating nature of gated developments in the urban realm. Furthermore, it has exposed gaps between the visions, goals and objectives of planning and the outcomes in practise. Additionally, it has revealed fragmentation between policies, plans and built environment professionals. Through this dissertation, I seek add to the current debate regarding gated developments and their implication on urban form. Furthermore, I address these findings through a review of the City of Cape Town's Gated Development Policy, as well as the harmonization and integration of relevant policies and plans.